Management Strategy for Optimizing Worker Wage Management through SDLC-Based Digital Transformation in Dodol Garut MSMEs - Yesti Siti Nurjanah; Reny Sumarni; Zaki Ulfatiatul R (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The wage management of daily workers in Micro, Small, and Medium Enterprises (MSMEs) often faces challenges due to manual record-keeping systems that are vulnerable to inaccuracies and delayed payments. This study aims to develop a digital wage management system using the System Development Life Cycle (SDLC) framework and to explore effective managerial strategies for optimizing payroll processes through digital transformation, with a case study at MSME PD. Intan Bestari. A qualitative descriptive approach was employed, incorporating data collection methods such as in-depth interviews, direct observation, and documentation analysis. The system development followed six structured SDLC phases: planning, analysis, design, implementation, testing, and maintenance. The research findings reveal that the developed system effectively automates various components of wage management, including employee attendance tracking, production output recording, wage calculation, and worker loan administration. The management strategies applied to support this system include an Operational Efficiency Strategy, which emphasizes process automation, standardization of administrative procedures, and centralized data handling to enhance accuracy and speed. Furthermore, a Digital Transformation Strategy was implemented by adopting SDLC-based technological solutions, ensuring system flexibility (agility), and enabling cross-functional integration between payroll, production, and procurement units. The implementation of this integrated digital system has significantly improved operational efficiency, reduced errors in data processing, accelerated wage disbursement, and enhanced transparency in wage administration at PD. Intan Bestari. This study offers valuable insights for MSMEs seeking to modernize their wage management practices, highlighting the critical role of strategic management in successful digital transformation.